Tafsir Methods in the Quran - Vera Diana Yulita; Andi Abd. Muis; Nurully Kesuma Ningrum; Janawati (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
Social facts show that the understanding of the Qur'an in society is very diverse, influenced by the culture, education, and interpretation methods used. Therefore, the study of the method of interpretation in the Qur'an is important so that Muslims can understand Islamic teachings accurately and in accordance with the context. This journal aims to identify and analyze the main interpretation methods in the study of the Qur'an, namely tahlili, ijmali, muqarin, and maudhui. This research uses a qualitative method with a literature review, examining primary and secondary sources related to the science of interpretation. This approach allows for a more in-depth analysis of the advantages and disadvantages of each method and its application in understanding the Qur'an. The results of the study show that the tahlili method discusses verses in detail, ijmali is concise and global, muqarin compares various interpretations, while maudhui examines certain themes in the Qur'an. By understanding this method of interpretation, it is hoped that the public can avoid misunderstandings in interpreting the verses of the Qur'an and develop broader insights. This study also contributes to the development of the science of interpretation so that it remains relevant to the changing times and the needs of Muslims.